Kolaborasi Komunikasi dalam Mempertahankan Citra pada Rumah Sakit Umum Daerah Arifin Achmad Provinsi Riau - Resty Amalia; Harliantara; Welly Wirman; Muhammad Firdaus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Good communication and teamwork are crucial to a hospital’s reputation. This study examines how communication and teamwork affect the image of Arifin Achmad Regional General Hospital in Riau, Indonesia. The method used was qualitative research with a case study approach, gathering data through interviews and hospital observations to understand the influence of communication on public perception using thematic data analysis. This study applies theories of image management, roles and strategies of communication, and image theory. This study also discusses teamwork methods to assess their effectiveness. Issues such as doctor-patient communication, communication management, and technological problems that hinder teamwork were also considered. This study highlights public perceptions of hospital management in the context of team communication collaboration. Recommendations for hospital management include improving services, enhancing performance, and providing team service training to boost the hospital’s image. This study helps us understand the impact of communication and teamwork on the hospital’s image and offers insights for hospital administrators, as well as for future research.